STRATEGIES IN ATTRACTING LOCAL LABOURS INTO MALAYSIAN CONSTRUCTION INDUSTRY - Nasyairi Mat Nasir; Zulkhairy Affandy Mohd Zaki; Sakinah Zun ‘Arif Hakim (Journal of Islamic, Social, Economics and Development, 2022)
With the expansion of the construction industry, there is a need to increase the volume of construction workers to meet the demand for construction industry development. However, many of the workers on the construction site are foreign labours. The overreliance on foreign workers makes Malaysia less independent and affects the Malaysian economy and society. Therefore, the aim of this study is to investigate the strategies to attract local construction workers into the Construction Industry. The objectives are to investigate the dependency factors of Malaysian construction companies towards foreign labours in the construction industry and to determine strategies in attracting the involvement of the local construction workforce. To achieve the best results for the study, a set of questionnaires has been distributed to the contractors in Malaysia. The result from the study has found that majority of the respondents agree with the variables set out for the factors to the over-reliance of foreign labours such as the shortages of local labours, low salary demanded by foreign labours and bad economic situation in their native country that leads to the increment of low-wage jobs. Therefore, broadening advertisement or marketing strategies by Akademi Binaaan Malaysia (ABM) for locals to participate in Malaysian construction industry, Increase the minimum monthly salary, provide allowances, and overtime payment and provide additional benefits are the top strategies that has been agreed by the contractors to attract local labours to get involve into construction industry.